Not dark yet - Robinson, Peter, 1950- (Robinson, Peter, 1950- Inspector Banks series., 2021)
Investigating the murder of a property developer in Yorkshire, Detective Chief Inspector Alan Banks and his team begin scanning the victim's security tapes only to discover that a brutal second crime was also captured.